2003
DOI: 10.1093/jn/133.10.3072
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Hormonal Stimulation of Rat Exocrine Pancreatic Function Regulates CRHSP-28 Phosphorylation In Vivo

Abstract: Dietary regulation of digestive enzyme secretion from the pancreas is essential for the breakdown of macronutrients in the gastrointestinal tract. Ca(2+)-responsive heat stable protein (CRHSP)-28 is a regulatory protein that modulates the exocytosis of digestive enzymes from pancreatic acinar cells. In the present study, isoelectric focusing and immunoblotting were used to characterize CRHSP-28 phosphorylation in isolated rat acinar cells and also after hormonal and dietary stimulation of rat pancreas in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In accordance with the effects of physiological secretagogues to induce D52 phosphorylation in vivo (17,23,24), when transfected into CHO-K1 cells, D52 undergoes a robust Ca 2ϩ -sensitive phosphorylation that coincides with its rapid accumulation along the plasma membrane. Consistent with a recent report (11), site-specific mutational analysis indicated that D52 phosphorylation occurs at serine 136.…”
mentioning
confidence: 68%
“…In accordance with the effects of physiological secretagogues to induce D52 phosphorylation in vivo (17,23,24), when transfected into CHO-K1 cells, D52 undergoes a robust Ca 2ϩ -sensitive phosphorylation that coincides with its rapid accumulation along the plasma membrane. Consistent with a recent report (11), site-specific mutational analysis indicated that D52 phosphorylation occurs at serine 136.…”
mentioning
confidence: 68%